2013
DOI: 10.1086/668915
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Volumetry for Noninvasive Measures of Phenotypic Flexibility during Digestion in Burmese Pythons

Abstract: Pythons are renowned for the profound phenotypical flexibility of their visceral organs in response to ingestion of large meals following prolonged fasting. Traditionally, the phenotypic changes are studied by determining organ mass of snakes killed at different times during digestion. Here we evaluate the use of magnetic resonance imaging (MRI) for in vivo measurements of the visceral organs in fasting and digesting snakes. Twelve snakes were MRI scanned immediately before the organs were removed and weighed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Andersen et al, 2005;Riquelme et al, 2011), and support the proposal that postprandial cardiac hypertrophy is a facultative response in pythons (Jensen et al, 2011;Hansen et al, 2013;Enok et al, 2013). In contrast, postprandial enlargement of the small intestine, liver and kidneys seems consistent amongst studies (Secor and Diamond, 1995;Secor and Diamond, 1998;Starck and Beese, 2001;Ott and Secor, 2007;Cox and Secor, 2008;Jensen et al, 2011;Hansen et al, 2013;Enok et al, 2013). Supporting the idea that expansion of the intestine is stimulated by the presence of chyme (Secor et al, 2000b), there was no effect of Hct reduction on the rise in intestinal mass during digestion, though it is impressive that significant intestinal hypertrophy occurs in animals with severe oxygen limitation.…”
Section: Adrenergic and Cholinergic Cardiac Tone In Fasting And Possupporting
confidence: 75%
See 1 more Smart Citation
“…Andersen et al, 2005;Riquelme et al, 2011), and support the proposal that postprandial cardiac hypertrophy is a facultative response in pythons (Jensen et al, 2011;Hansen et al, 2013;Enok et al, 2013). In contrast, postprandial enlargement of the small intestine, liver and kidneys seems consistent amongst studies (Secor and Diamond, 1995;Secor and Diamond, 1998;Starck and Beese, 2001;Ott and Secor, 2007;Cox and Secor, 2008;Jensen et al, 2011;Hansen et al, 2013;Enok et al, 2013). Supporting the idea that expansion of the intestine is stimulated by the presence of chyme (Secor et al, 2000b), there was no effect of Hct reduction on the rise in intestinal mass during digestion, though it is impressive that significant intestinal hypertrophy occurs in animals with severe oxygen limitation.…”
Section: Adrenergic and Cholinergic Cardiac Tone In Fasting And Possupporting
confidence: 75%
“…The universality and stimulus of the postprandial cardiac hypertrophy, however, remain unclear as Jensen et al found no postprandial cardiac hypertrophy in Burmese or Ball pythons (Python regius) under a similar experimental protocol (Jensen et al, 2011). They argued, therefore, that postprandial cardiac hypertrophy should be considered a 'facultative' rather than 'obligatory' response to feeding (Jensen et al, 2011), and the lack of postprandial cardiac hypertrophy was recently reported in two additional studies (Hansen et al, 2013;Enok et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fasting reptiles, however, ejection fraction is already very high (Burggren et al, 2013), leaving little capacity for further reductions in end-diastolic volume. Enhanced cardiac filling during diastole is therefore a more likely contributor, a view that is supported by magnetic resonance imaging, demonstrating substantial increases of end-diastolic heart volume during digestion in pythons and anacondas (Hansen et al, 2013;Zerbe et al, 2011). The increased cardiac filling must occur despite the shortened filling time that results from the postprandial tachycardia, and must therefore stem from increased venous return.…”
Section: Introductionmentioning
confidence: 93%
“…While the tachycardia stems from a combination of NANC (non-adrenergicnon-cholinergic) factors and a withdrawal of cholinergic tone (Enok et al, 2012;Skovgaard et al, 2009), the rise in V S remains more enigmatic. The postprandial increase of V S in pythons was originally ascribed to a rapid and extensive growth of the heart allowing for an elevated end-diastolic volume (Andersen et al, 2005;Secor and White, 2010), but a number of recent studies clearly demonstrate that heart mass does not increase during digestion (Hansen et al, 2013;Henriksen et al, 2014;Jensen et al, 2011;Slay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Within 24 h of ingestion of a meal, a python's small intestine doubles in mass (Secor, 1995;Secor and Diamond, 1995;Lignot et al, 2005) and volume (Hansen et al, 2013), and increases its mass-specific lipid content by 75% (Henriksen et al, 2015). A portion of this increase in lipid content is caused by the accumulation of lipid droplets in the apical side of the enterocytes during the first day of digestion (Starck and Beese, 2001;Lignot et al, 2005;Starck and Wimmer, 2005;Helmstetter et al, 2009).…”
Section: −1mentioning
confidence: 99%